Profil Gerakan Literasi di SDN Sidomukti Kabupaten Pati - Siti Imroatul Maghfiroh; Arfilia Wijayanti; Ferina Agustini (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
The purpose of this study is to find out the implementation of the School Literacy Movement, school literacy programs, and also student responses in implementing school literacy programs in Sidomukti Public Elementary School, Jaken District, Pati Regency. This study used a qualitative method with a descriptive approach, with data collection procedures in this study using interviews, questionnaires, observation, and documentation. The results showed that the School Literacy Movement at SD Negeri Sidomukti was already running. With the stages of the school literacy movement, namely the habituation stage, the development stage and the learning stage. activity 15 minutes before learning is one of the GLS activities. Through the support of existing school literacy programs such as digital literacy, literacy literacy, numeracy literacy, digital literacy, there are three activities, namely: short story breakfast, kids vlogger and sam mi sa si, literacy literacy and numeracy literacy. form of support in the implementation of the school literacy movement. The response of students who were very enthusiastic about participating in school activities played an important role in the implementation of school literacy activities. The results obtained can be said that the implementation of the school literacy movement has been running.